2018
DOI: 10.1002/lno.11019
|View full text |Cite
|
Sign up to set email alerts
|

Mixing and internal dynamics of a medium‐size and deep lake near the Arctic Circle

Abstract: The goal of the research was to identify the mixing features that distinguish wind forced, medium‐size fjord‐type lakes near the Arctic Circle from systems of similar geometry, but in a temperate climate. Experimental data and the results of 3D numerical hydrodynamic simulations were analyzed for Lake Lagarfljót (27 km long; 2 km wide; 110 m maximum depth; 65°N) during the 5‐month ice‐free period in 2009. The results showed that probably the most distinctive feature of arctic lakes is their low water column st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…Particle settling was assumed negligible following Striberger et al (2011), who argued that most of the sediments or rock flour brought by Jökulsá í Fljótsdal stays in suspension in the water in the summer and deposit during the winter. These assumptions were further supported by model results at the lake outflows which reproduce the evolution of the C SS signal measured at this site (RMSE = 0.011 kg m −3 and Figure A1 in Priet‐Mahéo et al, 2019). By neglecting particle settling in the simulations, convective sedimentation (e.g., Jazi & Wells, 2020) is not accounted for.…”
Section: Methodssupporting
confidence: 73%
See 3 more Smart Citations
“…Particle settling was assumed negligible following Striberger et al (2011), who argued that most of the sediments or rock flour brought by Jökulsá í Fljótsdal stays in suspension in the water in the summer and deposit during the winter. These assumptions were further supported by model results at the lake outflows which reproduce the evolution of the C SS signal measured at this site (RMSE = 0.011 kg m −3 and Figure A1 in Priet‐Mahéo et al, 2019). By neglecting particle settling in the simulations, convective sedimentation (e.g., Jazi & Wells, 2020) is not accounted for.…”
Section: Methodssupporting
confidence: 73%
“…The scaling function f ( We ) links the thermocline displacement (or wind set up) Δ H max and the time‐filtered Wedderburn number We (Appendix and see Shintani et al, 2010 for finite amplitude displacements). In the specific case of Lake Lagarfljót, the internal oscillations fade out quickly after the wind ceases (Priet‐Mahéo et al, 2019), so that the isopycnal displacements are largely associated with the magnitude and direction of the wind forcing. Hence, in these systems, one could also assume that the relevant time scale Δ t Ri , to check the quasi‐stationary assumption, is that of the wind forcing.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…With a Burger number on the order of unity, internal wave dynamics in Kempenfelt Bay are expected to be influenced by the Earth's rotation, which would manifest in the internal wave field. Similarly, Priet‐Mahéo et al () observed internal Kelvin waves in the long (27 km) and narrow (2 km) arctic Lake Lagarfljót (65°N, S i = O(10 −1 ) or O(1)) resulting in counterclockwise propagating temperature disturbances that decayed offshore. The influence of the Coriolis force upon the secondary thermocline tilt can be seen by looking at successive panels of Fig.…”
Section: Resultsmentioning
confidence: 81%